2005
DOI: 10.21000/jasmr05010487
|View full text |Cite
|
Sign up to set email alerts
|

Hydrologic Characterization of a Large Underground Mine Pool in Central Pennsylvania

Abstract: Major proposed changes in drainage control from a large underground mine pool required a detailed assessment of the hydrology, geochemistry, and impacts on the receiving streams. Proposed changes entail relocation of the withdrawal and treatment facilities to an adjoining, but separate watershed and increasing the pumping rate by 35%. Fifteen major and numerous smaller mines in two coal seams comprise the mine pool system. Degree of interconnection between mines ranges from horizontal and vertical seepage thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2005
2005
2006
2006

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…The L-15 mine-pool is in the Lower Kittanning coalbed, and is partially overlain by a second set of flooded mine-works in the Lower Freeport coalbed. The vertical interval between coals is around 50 m. The two mine-pools are hydraulically connected as shown by pumping and other data (Hawkins et al, 2005). Mine-works located near the crest of the two anticlines are not fully flooded, and water in these areas flows down-dip to recharge the main pool.…”
Section: Geologic and Hydrogeologic Settingmentioning
confidence: 89%
See 2 more Smart Citations
“…The L-15 mine-pool is in the Lower Kittanning coalbed, and is partially overlain by a second set of flooded mine-works in the Lower Freeport coalbed. The vertical interval between coals is around 50 m. The two mine-pools are hydraulically connected as shown by pumping and other data (Hawkins et al, 2005). Mine-works located near the crest of the two anticlines are not fully flooded, and water in these areas flows down-dip to recharge the main pool.…”
Section: Geologic and Hydrogeologic Settingmentioning
confidence: 89%
“…The L-15 mine-pool is also recharged by leakage through barrier pillars from adjoining flooded or partially flooded mines. About 30% of the flow at Duman is estimated to be barrier seepage from another mine-pool located to the east (Hawkins et al, 2005). Some ground water also enters the mine-pool through unmined strata.…”
Section: Geologic and Hydrogeologic Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…The main L-15 mine-pool is in the Lower Kittanning coalbed, and is partially overlain by a second set of flooded mine works in the Lower Freeport coalbed. The vertical interval between coals is around 50 m. The two mine-pools are hydraulically connected as shown by pumping and other data (Hawkins et al, 2005). Mine works located near the crest of the two anticlines are not fully flooded, and water in these areas flows down-dip to recharge the main pool.…”
Section: Geologic and Hydrogeologic Settingmentioning
confidence: 91%
“…In this paper we describe water quality trends and geochemical processes for iron and sulfate in a 35 year old mine-pool, Lancashire 15, that is about 79% flooded (approximately 4690 Ha). The physical hydrogeology is detailed in a companion paper (Hawkins et al, 2005) and information on pool volume and storage are used to interpret observed chemical trends. The mine-pool has one principal pumped discharge that yields over 24,000 L/min and has been sampled since closure and initial flooding.…”
Section: Introductionmentioning
confidence: 99%